Análise da dissicronia ventricular e da resposta neuro-humoral em portadores de marcapasso. - Claudia Drummond Guimaraes Abreu (2008)
The left bundle-branch block (LBBB) caused by right ventricular apicalpacing (RVP) by pacemaker (PM) can cause ventricular dyssynchrony (VD), neurohumoral activation and increased cardiac morbidity and mortality. The objective of this study is to assess whether the B type natriuretic peptide (BNP) identifies the presence of inter and intraventricular dyssynchrony in patients with PM. From June, 2007 to March 2008, 85 patients with uni or bicameral PM, pacemaker-dependent and with pattern of ventricular activation type LVBB were evaluated. Clinically stable patients in functional class I and II of the NYHA andwith left ventricular ejection fraction (LVEF) to 35% were included.Assessment of VD was performed using different echocardiographictechniques, including Tissue Synchronization Imaging (TSI), with analysis of the 12 segments. BNP was determined by using the Triage® BNP test (Biosite ® Inc., USA), while the echocardiogram was done, but with the examiner blind in relation to its results. The group was composed of 46 women (54%) and 39 men (46%) with a mean age of 58.5 ± 12.6 years. Forty-eight (57%) were Chagas' disease patients and 53 (62%) had arterial hypertension. The mean QRS duration was 139 ms, ranging from 120 to 180 ms. Complete atrioventricular block was the most frequent cause for the artificial implant and 74% of patients had dual chamber pacing (DDD). The mean LVEF was 51.8 ±8.5% and BNP was increased in 40% of the sample, using a cut-off of 60 pg/mL. Inter and intraventricular dyssynchrony have been identified in morethan 50% of the sample, through different echocardiographic techniques. A positive correlation was found between BNP and age (r=0.33, p=0002), LVEF (r= -0.28, p=0.010), systolic pressure in the pulmonary artery (PSAP: r=0.44, p<0.001) and pre-ejective time of the left ventricle (PETLV: r=0.38, p<0.001), which is index of intraventricular dyssynchrony. Multivariate linear regression analysis indicated that the plasma BNP levels were positively associated with age (p=0.024), LVEF (p<0.0001), PSAP (p=0.001) and PETLV (p=0.009). Subgroup analysis, Chagas disease patients and non-Chagas disease patients and, dual-chamber pacing (DDD) and ventricular pacing (VVI), showed no significant difference between clinical, electrocardiographic and echocardiographic findings. The results showed that RVP in pacemaker users, clinically stable and without significant left ventricular dysfunction, results in highfrequency of inter and intraventricular dissynchrony. In addition, theintraventricular dyssynchrony was an independent predictor of increased BNP, when measured by PETLV. The usefulness of the TSI to quantify ventricular dyssynchrony was found in the study, however there was no association between their measures and BNP, in this group of patients